The Penicillium chrysogenum tom1 Gene a Major Target of Transcription Factor MAT1-1-1 Encodes a Nuclear Protein Involved in Sporulation - Ramšak, Barbara; Kück, Ulrich (Frontiers in Fungal Biology, 2022)
Fungal mating-type loci (MAT) encode transcription factors (TFs) MAT1-1-1 and MAT1-2-1, which govern sexual reproduction as well as other developmental processes. In Penicillium chrysogenum, the major producer of the beta-lactam antibiotic penicillin, a recent chromatin immunoprecipitation followed by sequencing (ChIP-seq) analysis identified 254 genes as direct targets of MAT1-1-1, many of which encode thus far uncharacterized proteins. Here, we characterized one of the major targets of MAT1-1-1, the tom1 gene, which encodes a protein highly conserved within the group of Eurotiomycetes fungi. Using fluorescence microscopy, we demonstrated binding of MAT1-1-1 to the tom1 promoter by reporter gene analysis. Extensive electrophoretic mobility shift assays (EMSAs) further showed that the promoter sequence of tom1 is bound in vitro by both MAT1-1-1 and MAT1-2-1. This indicated an interaction between the two TFs, which was verified by yeast two-hybrid analysis. The sequence of tom1 carries a nuclear localization sequence, and indeed its nuclear localization was verified by fluorescence microscopy. The in vivo function of tom1 was investigated using tom1 deletion strains, as well as a complementing strain where the wild-type tom1 gene was reintroduced. We found a clear sporulation defect in the deletion strain, which became more evident when the fungi were grown at an elevated temperature of 31°C.